EVALUASI DAMPAK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT-MANDIRI PERDESAAN (PNPM-MdP)(STUDI IMPLEMENTASI DESA KERTA, KECAMATAN PAYANGAN,KABUPATEN GIANYAR) - Oka Diraka, I Wayan Raka (CITIZEN CHARTER, 2014)
ABSTRACT This research taking subject on Impact Evaluation of Indonesian Governmentâ€™s Community Empowerment Program called Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan (PNPM-MdP) which held on Kerta Village, Payangan District, Gianyar Regency. This village used to be count as underdeveloped village by The Government of Gianyar. The impact is mostly positive, like the community tends to have more critical minds recalled that the majority community of Balinese Village still had a traditional mind which is very tough, the program create a better infrastructure of the village. Hopefully, the government decide to extend the program which now has been issued to be stopped on 2015. Â Keywords : Evaluation, Impact, Participation, Policy, PNPM Mandiri Perdesaan